Women Contribution in the Historiography of Banten: Exploration of Artifactual, Textual, and Oral Traditions - Moh Ali Fadillah; Muhammad Ilham Gilang (IHiS (Indonesian Historical Studies), 2020)
Some studies are emphasized on the gender perspective to compose the historiography of Banten. The facts show that the protagonist of Indonesian historiography is always played by men: in political, economic, and social history. In many historical discourses, women considered too important. They 'exist' in history, but their 'presence' is often ignored in the shadow of male domination. The expectation is that writing gender-themed history in this perspective will be able to trigger early research, especially in the history of Banten. A women's story may appear in the manuscripts in the form of chronic or legend. This article reveals the role of Banten’s women in each historical event of Banten history and has the same right to be presented, so it should be ‘rewritten’. The explanation of the mental structure of each historical event related to that theme has been presented whether it is or not easier to interpret each event. By discussing it from artifactual, textual, and oral tradition evidence, I tried hypothetically to identify the role of women in the historiography of Banten. It clears to know that oral history and artefactual data that are very important in analyzing the role of women in the historiography of Banten.